Layered lattice iron bifunctional catalyst as well as preparation method and application thereof
By using a layered lattice iron bifunctional catalyst, using its unique structure and the aluminum-oxy-iron covalent bond to stabilize iron, the efficiency and stability of the Fenton catalyst in the prior art under low concentration wastewater treatment and low pH conditions is solved, and efficient organic pollutant degradation and catalyst recycling are achieved.
Patent Information
- Application Number
- CN202411943439.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing Fenton catalysts are inefficient when treating low concentrations of actual wastewater, and large amounts of iron-based active species are dissolved within the low pH range, resulting in a decrease in degradation and cycling performance.
A layered lattice iron bifunctional catalyst is used, which stabilizes the iron through aluminum-oxy-iron covalent bonds. It has a unique pore structure, a large specific surface area and a wide pore distribution. It can effectively adsorb and enrich organic pollutants in the water and reduce the iron dissolution amount during the oxidative degradation process.
It improves Fenton's oxidation and degradation efficiency, extends the service life of the catalyst, avoids the generation of iron sludge, and ensures the continuous progress and recycling of the reaction.
Smart Images

Figure CN119657143A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of Fenton catalysts, and more specifically, to a layered lattice iron bifunctional catalyst and a preparation method and application thereof. Background Art
[0002] With the rapid development of textile, paper, plastic, leather, electrolysis, resin, rubber and other chemical industries, various industrial products have greatly enriched people's lives, but the wastewater discharge that comes with it has directly affected the ecological environment and seriously threatened human health. Therefore, it is particularly urgent and important to develop an efficient and environmentally friendly treatment material and technology to promote the sustainable development of resources.
[0003] At present, many technologies for treating organic pollutants have been proposed at home and abroad, including adsorption, membrane separation, biodegradation, advanced oxidation and photocatalysis. Among them, advanced oxidation, especially Fenton-like heterogeneous oxidation, has attracted much attention due to its economic sustainability, environmental friendliness and ability to completely degrade various organic pollutants in water. So far, iron-based catalysts have become one of the most commonly used Fenton catalysts due to their high catalytic performance and low cost. For example, AMMesquita, IR GMMDCastro,MA TC Ramalho, MC Guerreiro, Appl. Catal. BEnviron. 2016, 192, 286-295. Goethite-derived iron oxide (Gt-B1×4) was used to remove the organic dye methylene blue from water. On the one hand, adsorption technology helps to enrich low-concentration pollutants on the catalyst surface, thereby accelerating the Fenton oxidation process, and on the other hand, it also realizes the in-situ regeneration of the catalyst. Therefore, many researchers have prepared iron-based catalysts through composite structures to improve the Fenton oxidation degradation efficiency. For example, the document P. Zhou, Z. Dai, T. Lu, X. Ru, M. A. Ofori, W. Yang, J. Hou, H. Jin, Catalysts, 2022, 12, 669 prepared an iron-loaded attapulgite Fenton catalyst for removing rhodamine B from water; the document C. Wang, R. Sun, R. Huang, J. Clean. Prod. 2021, 297, 126681 removed rhodamine B from water by doping biochar with iron, but it still had the problem of loss of active species leading to decreased cycle performance.
[0004] In summary, there are two main challenges in the practical application of common Fenton catalysts: (1) low efficiency in treating low-concentration actual wastewater; (2) large amounts of iron-based active species are dissolved in the low pH range to form iron sludge, which leads to the degradation and cycle performance of Fenton catalysts. Therefore, how to solve the above challenges faced by Fenton catalysts and design and develop high-performance, high-stability and low-cost Fenton catalysts has become a research hotspot and focus. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present application provides a layered lattice iron bifunctional catalyst and its preparation method and application. The layered lattice iron bifunctional catalyst provided in the present application has a unique pore structure, a large specific surface area and a wide pore distribution, which can effectively adsorb organic pollutants in water and enrich them on the surface of the material, providing a driving force for the Fenton oxidation degradation of low-concentration organic pollutants and improving the Fenton oxidation degradation efficiency; the layered lattice Fe exists in the catalyst as an aluminum-oxygen-iron (Al-O-Fe) covalent bond, the stability of Fe is improved, the amount of Fe dissolution during the oxidation degradation process is extremely low, and no iron mud is produced, which is conducive to the continuous removal reaction and recycling.
[0006] In order to achieve the above objectives, in a first aspect, the present application provides a method for preparing a layered lattice iron bifunctional catalyst, comprising the following steps:
[0007] Step 1: uniformly mix the layered structure material and deionized water to obtain a slurry, add the slurry to a nucleation reactor and stir vigorously, add the stirred slurry again to the nucleation reactor and continue stirring, and repeat for multiple times; then collect the slurry for centrifugation, and vacuum dry the solid material obtained by centrifugation to obtain a purified and size-selected material;
[0008] Step 2: Calcine the material obtained in step 1 at high temperature to undergo structural evolution, thereby obtaining a layered lattice iron bifunctional catalyst.
[0009] Furthermore, the layered structure material in step 1 includes any one of iron-containing attapulgite and iron-based hydrotalcite, or a combination of both.
[0010] Preferably, the relative content of Fe in the layered structure material in step 1 is 10.83wt.% to 20.48wt.%.
[0011] Furthermore, the mass ratio of the layered structure material to deionized water is 1:1000 to 1:100.
[0012] Furthermore, the mass of the layered structure material in step 1 is 1 to 25000 g.
[0013] Furthermore, the parameters of the nucleation reactor in step 1 are set as follows: stator and rotor slit width 0.05-0.5 mm, rotation speed 100-3000 rpm.
[0014] Furthermore, the number of cycles in step 1 is 2 to 10 times.
[0015] Furthermore, in step 1, the drying temperature is 60° C. and the drying time is 6 hours.
[0016] Furthermore, in step 2, the high temperature calcination temperature is 150-700° C., the holding time is 1-5 hours, and the heating rate is 4-10° C. / min.
[0017] In a second aspect, the present invention provides a layered lattice iron bifunctional catalyst prepared by the above-mentioned preparation method.
[0018] Furthermore, the layered lattice iron bifunctional catalyst has a Zeta potential of -32.26 to 45.16 mV and a specific surface area of 63.97 to 146.98 m 2 / g, and the pore size is 13.34~26.89nm.
[0019] Furthermore, the molar ratio of divalent iron / trivalent iron (Fe(II) / Fe(III)) in the layered lattice iron bifunctional catalyst is 0.54-1.94.
[0020] In a third aspect, the present invention provides the use of the above-mentioned layered lattice iron bifunctional catalyst in the degradation and removal of organic pollutants.
[0021] Furthermore, the method for degrading and removing organic pollutants comprises the following steps:
[0022] Step S1: Selecting organic pollutants, and adjusting the concentration and pH of the pollutant solution;
[0023] Step S2: adjusting the temperature of the reaction system;
[0024] Step S3: Add the layered lattice iron bifunctional catalyst into the pollutant solution, perform the first oscillation, and then add H2O2 to perform the second oscillation to make it react completely, thereby achieving the removal of organic pollutants.
[0025] Preferably, the organic pollutant in step S1 is a mixture of any one or more of methylene blue, methyl orange, Congo red, rhodamine B, tetracycline hydrochloride, doxycycline hydrochloride, ciprofloxacin, phenol, bisphenol A or 2,4-dichlorophenol; the concentration of the pollutant solution is adjusted to 10 to 30,000 mg / L, the volume is 0.05 to 2 L, and the pH of the pollutant solution is 2 to 14.
[0026] More preferably, 1 M sulfuric acid or sodium hydroxide is used to adjust the pH of the pollutant solution.
[0027] Preferably, the temperature of the reaction system in step S2 is 20-80°C.
[0028] Preferably, in step S3, the first oscillation time is 0 to 120 min; the purity of H2O2 is 10 wt.% to 30 wt.%, the mass fraction ratio of H2O2 to layered lattice iron bifunctional catalyst is 1:100 to 1:10; and the second oscillation time is 0 to 120 min.
[0029] More preferably, the first oscillation and the second oscillation are both performed under dark conditions.
[0030] Preferably, the method for degrading and removing organic pollutants also includes recovering the layered lattice iron bifunctional catalyst, specifically by filtering the layered lattice iron bifunctional catalyst mixed solution after the reaction through a 0.22 μm filter membrane, washing the residual organic matter on the surface with deionized water, and drying it at 60° C. under vacuum conditions for 6 hours.
[0031] The technical solution provided by this application has at least the following beneficial effects compared with the prior art:
[0032] 1) The present invention utilizes a nucleation reactor to disperse and size-control layered structural materials (iron-containing attapulgite clay minerals, iron-based hydrotalcite), and then activates the crystals of the materials through structural evolution, adjusts the controllable exposure of iron and the valence ratio of iron, and obtains a layered lattice iron bifunctional catalyst; the present invention innovatively and controllably synthesizes a bifunctional catalyst rich in layered lattice iron, and applies it to adsorption-Fenton coupled degradation to remove organic pollutants in water, achieving theoretical guidance for practical application;
[0033] 2) The layered lattice Fe bifunctional catalyst prepared by the present invention has a unique pore structure, a large specific surface area and a wide pore distribution. It can effectively adsorb organic pollutants in water during use and enrich them on the surface of the material, providing a driving force for the Fenton oxidation degradation of low-concentration organic pollutants and improving the Fenton oxidation degradation efficiency;
[0034] 3) The layered lattice Fe of the present invention is stably present in the catalyst through the Al-O-Fe covalent bond, the stability of Fe is improved, the amount of Fe dissolved during the oxidation degradation process is extremely low, and no iron mud is generated, which is conducive to the continuous removal reaction and recycling;
[0035] 4) When the catalyst of the present invention performs a removal reaction, H2O2 adsorbed on the catalyst surface can be activated in situ by the catalyst, thereby generating hydroxyl radicals, shortening the distance between the hydroxyl radicals and the pollutants; at the same time, the electron transfer between the layered lattice Fe of the present invention between the organic pollutant-catalyst-H2O2 is accelerated, promoting the reduction of Fe(III) on the catalyst surface to Fe(II), accelerating the Fe(III) / Fe(II) cycle, increasing the Fenton reaction catalytic degradation rate, and increasing the degree of mineralization degradation of organic pollutants;
[0036] 5) The layered lattice iron bifunctional catalyst of the present invention achieves a certain degree of in-situ regeneration without the need for elution with organic solvents, acids or bases. The process is simple to operate, flexible in form and does not produce toxic or harmful by-products. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The data diagram is a graph of the iron phase composition characterization of the sample of Example 1 using a 500A Mössbauer spectrometer from Topologic Systems;
[0038] Figure 2 The data diagram is a crystal structure characterization data of the sample of Example 1 using an XRD-6000 X-ray powder diffractometer;
[0039] Figure 3 A structural model diagram of the sample of Example 1 constructed using the software Vesta;
[0040] Figure 4 This is a data diagram of group characterization of the sample in Example 1 using a TENSORⅡ Fourier transform infrared spectrometer;
[0041] Figure 5 This is a data diagram showing the Fe valence state characterization of the sample in Example 1 using an X-ray photoelectron spectrometer from Thermo Fisher;
[0042] Figure 6 This is a data graph showing the pore structure of the sample in Example 1 using a 3QDS-MP-30 specific surface area and pore size analyzer. DETAILED DESCRIPTION
[0043] In order to enable those skilled in the art to understand the present application more clearly, the present application is further described in detail below in conjunction with examples and drawings. However, it should be understood that the following examples are only preferred implementation methods of the present application, and the scope of protection required by the present application shall be based on the scope defined in the claims.
[0044] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0045] <Example>
[0046] Example 1
[0047] A layered lattice iron bifunctional catalyst is prepared by the following method:
[0048] Step 1: 5 g of attapulgite with an iron content of 14.64 wt.% was mixed with 5000 mL of deionized water to obtain a slurry, the stator rotor slit width of the nucleation reactor was set to 0.3 mm, the rotation speed was set to 500 rpm, the slurry was added to the nucleation reactor and stirred vigorously, the stirred slurry was added to the nucleation reactor again and continued to be stirred, and the cycle was repeated 6 times; the slurry was then collected and centrifuged, and the solid material obtained by centrifugation was dried at 60° C. in vacuum to obtain a purified and size-selected material;
[0049] Step 2: Set the heating rate to 5°C / min, and calcine the material obtained in step 1 at 150°C for 4 hours to achieve structural evolution.
[0050] test:
[0051] 1. The iron phase composition of the sample was characterized using a 500A Mössbauer spectrometer from Japan Topologic Systems. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that iron composition includes Fe(II), Fe(III) and Fe2O3.
[0052] 2. The crystal structure of the sample was characterized and refined using the XRD-6000 X-ray powder diffractometer from Shimadzu Corporation. The results are as follows: Figure 2 As shown, the structural model was further constructed according to the software Vesta, and the results are shown in Figure 3 As shown. Figure 2 and Figure 3 It can be seen that the iron in the catalyst exists in the form of MO-Fe bond, and the metal M is Mg or Al.
[0053] 3. The samples were characterized by using the TENSORⅡ Fourier transform infrared spectrometer from Bruker, Germany. Figure 4 As shown. Figure 4 It can be seen that the iron in the catalyst exists in the form of Al-O-Fe bonds.
[0054] 4. The X-ray photoelectron spectrometer of Thermo Company of the United States was used to characterize the Fe valence state of the sample. The results are as follows Figure 5 As shown. Figure 5 It can be seen that the Fe(II) / Fe(III) molar ratio is 0.79.
[0055] 5. The 3QDS-MP-30 surface area and pore size analyzer from Quantachrome, USA, was used to characterize the pore structure of the samples. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the specific surface area and average pore size of the catalyst are 146.98 m 2 / g and 13.34nm.
[0056] 6. The surface properties of the sample were characterized using the Zetasizer Nano ZS nanoparticle size and Zeta potential instrument from Malvern Instruments, UK. The test result showed that the Zeta potential was -6.88 mV.
[0057] From the above tests, it can be seen that the layered lattice Fe bifunctional catalyst prepared in this example has the potential to be used as an adsorption and Fenton catalyst.
[0058] Example 2
[0059] A layered lattice iron bifunctional catalyst is prepared by the following method:
[0060] Step 1: 10 g of attapulgite with an iron content of 10.83 wt.% was mixed with 1000 mL of deionized water to obtain a slurry, the stator rotor slit width of the nucleation reactor was set to 0.15 mm, and the rotation speed was set to 1500 rpm, the slurry was added to the nucleation reactor and stirred vigorously, and the stirred slurry was added to the nucleation reactor again and continued to be stirred, and the cycle was repeated 8 times; the slurry was then collected and centrifuged, and the solid material obtained by centrifugation was dried at 60° C. in vacuum to obtain a purified and size-selected material;
[0061] Step 2: Set the heating rate to 6°C / min, and calcine the material obtained in step 1 at 450°C for 5 hours to achieve structural evolution.
[0062] The same method as in Example 1 was used to carry out relevant tests. The results showed that the iron in the obtained layered lattice iron bifunctional catalyst existed in the form of Al-O-Fe bonds, the iron composition included Fe(II), Fe(III) and Fe2O3, the Fe(II) / Fe(III) ratio was 1.22, the Zeta potential was -20.09 mV, the specific surface area and the average pore size were 63.97 m 2 / g and 25.98nm.
[0063] Example 3
[0064] A layered lattice iron bifunctional catalyst is prepared by the following method:
[0065] Step 1: 1 g of aluminum-iron hydrotalcite with an iron content of 13.17 wt.% was mixed with 500 mL of deionized water to obtain a slurry, the stator rotor slit width of the nucleation reactor was set to 0.05 mm, the rotation speed was set to 100 rpm, the slurry was added to the nucleation reactor and stirred vigorously, the stirred slurry was added to the nucleation reactor again and continued to be stirred, and the cycle was repeated twice; the slurry was then collected and centrifuged, and the solid material obtained by centrifugation was dried at 60° C. in vacuum to obtain a purified and size-selected material;
[0066] Step 2: Set the heating rate to 4°C / min, and calcine the material obtained in step 1 at 650°C for 2 hours to achieve structural evolution.
[0067] The same method as in Example 1 was used to carry out relevant tests. The results showed that the iron in the obtained layered lattice Fe bifunctional catalyst existed in the form of Al-O-Fe bonds, the iron composition included Fe(II), Fe(III) and Fe2O3, the Fe(II) / Fe(III) ratio was 1.64, the Zeta potential was 45.16 mV, the specific surface area and the average pore size were 75.82 m 2 / g and 14.11nm.
[0068] Example 4
[0069] A layered lattice iron bifunctional catalyst is prepared by the following method:
[0070] Step 1: 25000g of attapulgite with an iron content of 15.79wt.% is mixed evenly with 2500L of deionized water to obtain a slurry, the stator rotor slit width of the nucleation reactor is set to 0.35mm, the rotation speed is set to 2000rpm, the slurry is added to the nucleation reactor and stirred vigorously, the stirred slurry is added to the nucleation reactor again and stirred continuously, and the cycle is repeated 10 times; the slurry is then collected and centrifuged, and the solid material obtained by centrifugation is dried at 60°C in vacuum to obtain a purified and size-selected material;
[0071] Step 2: Set the heating rate to 10°C / min, and calcine the material obtained in step 1 at 700°C for 1 hour to achieve structural evolution.
[0072] The same method as in Example 1 was used to carry out relevant tests. The results showed that the iron in the obtained layered lattice Fe bifunctional catalyst existed in the form of Al-O-Fe bonds, the iron composition included Fe(II), Fe(III) and Fe2O3, the Fe(II) / Fe(III) ratio was 1.94, the Zeta potential was -32.26 mV, the specific surface area and average pore size were 75.89 m 2 / g and 26.89nm.
[0073] Example 5
[0074] A layered lattice iron bifunctional catalyst is prepared by the following method:
[0075] Step 1: 1000 g of aluminum-iron hydrotalcite with an iron content of 20.48 wt.% was mixed with 200 L of deionized water to obtain a slurry, the stator rotor slit width of the nucleation reactor was set to 0.5 mm, the rotation speed was set to 3000 rpm, the slurry was added to the nucleation reactor and stirred vigorously, the stirred slurry was added to the nucleation reactor again and continued to be stirred, and the cycle was repeated 5 times; the slurry was then collected and centrifuged, and the solid material obtained by centrifugation was dried at 60° C. in vacuum for 6 h to obtain a purified and size-selected material;
[0076] Step 2: Set the heating rate to 8°C / min, and calcine the material obtained in step 1 at 250°C for 3 hours to achieve structural evolution.
[0077] The same method as in Example 1 was used to carry out relevant tests. The results showed that the iron in the obtained layered lattice Fe bifunctional catalyst existed in the form of Al-O-Fe bonds, the iron composition included Fe(II) and Fe(III), the Fe(II) / Fe(III) ratio was 0.54, the Zeta potential was 35.11 mV, the specific surface area and the average pore size were 104.77 m 2 / g and 18.15nm.
[0078] Example 6
[0079] Application of layered lattice iron bifunctional catalysts in the degradation and removal of organic pollutants:
[0080] Tetracycline hydrochloride (TCH) was selected as the target pollutant, and its solution concentration was adjusted to 50 mg / L, the solution volume was 0.1 L, 1 M sulfuric acid was used to adjust the pH to 4, the reaction system temperature was set to 30°C, 0.07 g of the layered lattice iron bifunctional catalyst obtained in Examples 1-5 was respectively put into the TCH solution, and the first oscillation was carried out for 60 min in a 150 rpm shaker under dark conditions, 0.7 mg of 30 wt.% H2O2 was added, and the second oscillation was carried out for 120 min to achieve the removal of organic pollutants. The removal performance is shown in Table 1 (i.e., after a single experiment in Table 1).
[0081] The mixed solution of the layered lattice iron bifunctional catalyst after the reaction was filtered through a 0.22 μm filter membrane, the residual organic matter on the surface was washed with deionized water, and dried at 60°C under vacuum conditions. The recovered layered lattice iron bifunctional catalyst was re-added to the pollutant solution to cyclically degrade and remove organic pollutants. The removal performance after 20 cycles is shown in Table 1 (i.e., after 20 cycles in Table 1).
[0082] It can be seen from Table 1 that for a single experiment, the removal efficiencies of Examples 1-5 are 75.40%, 77.60%, 80.37%, 85.20% and 98.15%, respectively; the COD removal rates are 46.29%, 49.40%, 58.11%, 65.26% and 76.84%, respectively; and the iron dissolution amounts are 0.0009, 0.0010, 0.0013, 0.0023 and 0.0011 mg / L, respectively. For 20 cycles: the removal efficiency of Examples 1-5 can still reach 70.39%, 73.74%, 78.53%, 82.19% and 90.35% respectively; the COD removal rate can still reach 41.56%, 40.41%, 52.41%, 60.16% and 70.18% respectively; the iron dissolution amount can still be as low as 0.0018, 0.0020, 0.0023, 0.0037 and 0.0031 mg / L. The total volume of pollutants treated this time is 2L.
[0083] Example 7
[0084] Application of layered lattice iron bifunctional catalysts in the degradation and removal of organic pollutants:
[0085] Doxycycline hydrochloride (DCH) was selected as the target pollutant, and its solution concentration was adjusted to 20 mg / L, the solution volume was 0.5 L, 1 M sulfuric acid was used to adjust the pH to 4, the reaction system temperature was set to 35 ° C, 0.05 g of the layered lattice iron bifunctional catalyst obtained in Example 1 was put into the DCH solution, and the first oscillation was carried out in a 150 rpm shaker under dark conditions for 120 min, 5.0 mg of 10 wt.% H2O2 was added, and the second oscillation was carried out for 120 min to achieve the removal of organic pollutants. The removal efficiency, COD removal rate and iron dissolution amount were 92.74%, 70.47% and 0.0020 mg / L respectively.
[0086] The mixed solution of the layered lattice iron bifunctional catalyst after the reaction was filtered through a 0.22μm filter membrane, the residual organic matter on the surface was washed with deionized water, and dried at 60°C under vacuum conditions. The recovered layered lattice iron bifunctional catalyst was re-added to the pollutant solution to cyclically degrade and remove organic pollutants. After 50 cycles, the removal efficiency, COD removal rate and iron dissolution amount were 86.73%, 65.53% and 0.0137mg / L, and the total volume of pollutants treated this time reached 25L.
[0087] Example 8
[0088] Application of layered lattice iron bifunctional catalysts in the degradation and removal of organic pollutants:
[0089] Methylene blue (MB) was selected as the target pollutant, and its solution concentration was adjusted to 500 mg / L, the solution volume was 0.2 L, the pH was adjusted to 2 using 1 M sulfuric acid, the temperature of the reaction system was set to 60° C., 0.10 g of the layered lattice iron bifunctional catalyst obtained in Example 2 and 10 mg of 25 wt.% H2O2 were added to the MB solution, and the solution was shaken in a shaker at 150 rpm in the dark for 60 min to achieve the removal of organic pollutants, and the removal efficiency, COD removal rate and iron dissolution amount were 100.00%, 82.47% and 0.0048 mg / L, respectively;
[0090] The mixed solution of the layered lattice iron bifunctional catalyst after the reaction was filtered through a 0.22μm filter membrane, the residual organic matter on the surface was washed with deionized water, and dried at 60°C under vacuum conditions. The recovered layered lattice iron bifunctional catalyst was re-added to the pollutant solution to cyclically degrade and remove organic pollutants. After 100 cycles, the removal efficiency, COD removal rate and iron dissolution amount were 93.77%, 75.53% and 0.0217mg / L, and the total volume of pollutants treated this time reached 20L.
[0091] Example 9
[0092] Application of layered lattice iron bifunctional catalysts in the degradation and removal of organic pollutants:
[0093] Methyl orange (MO) was selected as the target pollutant, and its solution concentration was adjusted to 200 mg / L, the solution volume was 0.4 L, the pH was adjusted to 10 using 1 M sulfuric acid, the reaction system temperature was set to 50° C., 0.10 g of the layered lattice iron bifunctional catalyst obtained in Example 3 and 2.5 mg of 15 wt.% H2O2 were added to the MO solution, and the solution was shaken in a shaker at 150 rpm in the dark for 100 min to achieve the removal of organic pollutants, and the removal efficiency, COD removal rate and iron dissolution amount were 93.28%, 76.37% and 0.0036 mg / L, respectively;
[0094] The mixed solution of the layered lattice iron bifunctional catalyst after the reaction was filtered through a 0.22μm filter membrane, the residual organic matter on the surface was washed with deionized water, and dried at 60°C under vacuum conditions. The recovered layered lattice iron bifunctional catalyst was re-added to the pollutant solution to cyclically degrade and remove organic pollutants. After 50 cycles, the removal efficiency, COD removal rate and iron dissolution amount were 89.39%, 65.94% and 0.0162mg / L, and the total volume of pollutants treated this time reached 20L.
[0095] Example 10
[0096] Application of layered lattice iron bifunctional catalysts in the degradation and removal of organic pollutants:
[0097] Ciprofloxacin (CIP) was selected as the target pollutant, and its solution concentration was adjusted to 10 mg / L, the solution volume was 0.05 L, the pH was adjusted to 7 using 1 M sulfuric acid, the reaction system temperature was set to 20° C., 0.02 g of the layered lattice iron bifunctional catalyst obtained in Example 4 was put into the CIP solution, and the first oscillation was performed at 150 rpm in a shaker under dark conditions for 60 min, 1 mg of 30 wt.% H2O2 was added, and the second oscillation was performed for 30 min to achieve the removal of organic pollutants, and the removal efficiency, COD removal rate and iron dissolution amount were 82.11%, 50.23% and 0.0010 mg / L, respectively;
[0098] The mixed solution of the layered lattice iron bifunctional catalyst after the reaction was filtered through a 0.22μm filter membrane, the residual organic matter on the surface was washed with deionized water, and dried at 60°C under vacuum conditions. The recovered layered lattice iron bifunctional catalyst was re-added to the pollutant solution to cyclically degrade and remove organic pollutants. After 60 cycles, the removal efficiency, COD removal rate and iron dissolution amount were 77.24%, 45.82% and 0.0018mg / L, and the total volume of pollutants treated this time reached 3L.
[0099] Embodiment 11
[0100] Application of layered lattice iron bifunctional catalysts in the degradation and removal of organic pollutants:
[0101] Congo red (CR) was selected as the target pollutant, and its solution concentration was adjusted to 100 mg / L, the solution volume was 1 L, 1 M sulfuric acid was used to adjust the pH to 6, the reaction system temperature was set to 70°C, 0.15 g of the layered lattice iron bifunctional catalyst obtained in Example 5 was added to the CR solution, and the first oscillation was performed at 150 rpm in a shaker under dark conditions for 30 min, 1.5 mg of 20 wt.% H2O2 was added, and the second oscillation was performed for 30 min to achieve the removal of organic pollutants, and the removal efficiency, COD removal rate and iron dissolution amount were 96.63%, 73.48% and 0.0043 mg / L, respectively;
[0102] The mixed solution of the layered lattice iron bifunctional catalyst after the reaction was filtered through a 0.22μm filter membrane, the residual organic matter on the surface was washed with deionized water, and dried at 60°C under vacuum conditions. The recovered layered lattice iron bifunctional catalyst was re-added to the pollutant solution to cyclically degrade and remove organic pollutants. After 50 cycles, the removal efficiency, COD removal rate and iron dissolution amount were 95.14%, 70.63% and 0.0093mg / L, and the total volume of pollutants treated this time reached 50L.
[0103] Example 12
[0104] Application of layered lattice iron bifunctional catalysts in the degradation and removal of organic pollutants:
[0105] Rhodamine B (Rh B) was selected as the target pollutant, and its solution concentration was adjusted to 400 mg / L, the solution volume was 0.15 L, the pH was adjusted to 10 using 1 M sulfuric acid, the temperature of the reaction system was set to 25° C., 0.08 g of the layered lattice iron bifunctional catalyst obtained in Example 5 was put into the Rh B solution, and the first oscillation was performed at 150 rpm in a shaker under dark conditions for 60 min, 2.0 mg of 25 wt.% H2O2 was added, and the second oscillation was performed for 60 min to achieve the removal of organic pollutants, and the removal efficiency, COD removal rate and iron dissolution amount were 94.28%, 77.33% and 0.0013 mg / L, respectively;
[0106] The mixed solution of the layered lattice iron bifunctional catalyst after the reaction was filtered through a 0.22μm filter membrane, the residual organic matter on the surface was washed with deionized water, and dried at 60°C under vacuum conditions. The recovered layered lattice iron bifunctional catalyst was re-added to the pollutant solution to cyclically degrade and remove organic pollutants. After 20 cycles, the removal efficiency, COD removal rate and iron dissolution amount were 90.31%, 72.22% and 0.0081mg / L, and the total volume of pollutants treated this time reached 3L.
[0107] Embodiment 13
[0108] Application of layered lattice iron bifunctional catalysts in the degradation and removal of organic pollutants:
[0109] Phenol was selected as the target pollutant, and its solution concentration was adjusted to 15000 mg / L, the solution volume was 2 L, the pH was adjusted to 14 using 1 M sulfuric acid, the temperature of the reaction system was set to 60° C., 6 g of the layered lattice iron bifunctional catalyst obtained in Example 3 was put into the Phenol solution, and the first oscillation was performed for 120 min at 150 rpm in a shaking table under dark conditions, 60 mg of 23.6 wt.% H2O2 was added, and the second oscillation was performed for 90 min to achieve the removal of organic pollutants, and the removal efficiency, COD removal rate and iron dissolution amount were 98.16%, 72.47% and 0.0069 mg / L, respectively;
[0110] The mixed solution of the layered lattice iron bifunctional catalyst after the reaction was filtered through a 0.22μm filter membrane, the residual organic matter on the surface was washed with deionized water, and dried at 60°C under vacuum conditions. The recovered layered lattice iron bifunctional catalyst was re-added to the pollutant solution to cyclically degrade and remove organic pollutants. After 50 cycles, the removal efficiency, COD removal rate and iron dissolution amount were 89.24%, 65.53% and 0.0101mg / L, and the total volume of pollutants treated this time reached 100L.
[0111] Embodiment 14
[0112] Application of layered lattice iron bifunctional catalysts in the degradation and removal of organic pollutants:
[0113] Bisphenol A (BPA) was selected as the target pollutant, and its solution concentration was adjusted to 30000 mg / L, the solution volume was 1 L, 1 M sulfuric acid was used to adjust the pH to 3, the reaction system temperature was set to 80° C., 2.5 g of the layered lattice iron bifunctional catalyst obtained in Example 4 was added to the BPA solution, and the first oscillation was performed at 150 rpm in a shaker under dark conditions for 90 min, 60 mg of 30 wt.% H2O2 was added, and the second oscillation was performed for 120 min to achieve the removal of organic pollutants, and the removal efficiency, COD removal rate and iron dissolution amount were 96.74%, 72.30% and 0.0048 mg / L respectively;
[0114] The mixed solution of the layered lattice iron bifunctional catalyst after the reaction was filtered through a 0.22μm filter membrane, the residual organic matter on the surface was washed with deionized water, and dried at 60°C under vacuum conditions. The recovered layered lattice iron bifunctional catalyst was re-added to the pollutant solution to cyclically degrade and remove organic pollutants. After 100 cycles, the removal efficiency, COD removal rate and iron dissolution amount were 82.79%, 50.35% and 0.0042mg / L, and the total volume of pollutants treated this time reached 100L.
[0115] Embodiment 15
[0116] Application of layered lattice iron bifunctional catalysts in the degradation and removal of organic pollutants:
[0117] 2,4-dichlorophenol (2,4-DCP) was selected as the target pollutant, and its solution concentration was adjusted to 10 mg / L, the solution volume was 1 L, 1 M sulfuric acid was used to adjust the pH to 6, the reaction system temperature was set to 40°C, 2.5 g of the layered lattice iron bifunctional catalyst obtained in Example 4 was put into the 2,4-DCP solution, and the first oscillation was performed in a 150 rpm shaker under dark conditions for 90 min, 60 mg of 30 wt.% H2O2 was added, and the oscillation was performed for 0 min to achieve the removal of organic pollutants, and the removal efficiency, COD removal rate and iron dissolution amount were 86.54%, 52.30% and 0.0018 mg / L respectively;
[0118] The mixed solution of the layered lattice iron bifunctional catalyst after the reaction was filtered through a 0.22μm filter membrane, the residual organic matter on the surface was washed with deionized water, and dried at 60°C under vacuum conditions. The recovered layered lattice iron bifunctional catalyst was re-added to the pollutant solution to cyclically degrade and remove organic pollutants. After 100 cycles, the removal efficiency, COD removal rate and iron dissolution amount were 82.88%, 49.15% and 0.0022mg / L, and the total volume of pollutants treated this time reached 100L.
[0119] Comparative Example 1
[0120] The application of the catalyst provided in this comparative example in the degradation and removal of organic pollutants is roughly the same as that in Example 8, with the main difference being that the catalyst used in this comparative example 1 is replaced by an impregnation method [refer to the document Magnetic Activated-ATP@Fe3O4 Nanocomposite as an Efficient Fenton-Like Heterogeneous Catalyst for Degradation of Ethidium Bromide. Sci. Rep. 7, 6070 (2017).] in which iron oxide is loaded on a attapulgite material (the iron content of attapulgite is about 2 wt.%).
[0121] After a single experiment, the removal efficiency, COD removal rate and iron dissolution amount of this comparative example were 68.79%, 37.46% and 1.3796 mg / L respectively; after 100 cycles, the removal efficiency, COD removal rate and iron dissolution amount were 33.17%, 17.65% and 17.65 mg / L respectively.
[0122] Table 1
[0123]
Claims
1. A method for preparing a layered lattice iron bifunctional catalyst, characterized in that: The following steps are involved: Step 1: uniformly mix the layered structure material and deionized water to obtain a slurry, add the slurry to a nucleation reactor and stir vigorously, add the stirred slurry again to the nucleation reactor and continue stirring, and repeat for multiple times; then collect the slurry for centrifugation, and vacuum dry the solid material obtained by centrifugation to obtain a purified and size-selected material; Step 2: Calcine the material obtained in step 1 at high temperature to undergo structural evolution, thereby obtaining a layered lattice iron bifunctional catalyst.
2. The method for preparing the layered lattice iron bifunctional catalyst according to claim 1, characterized in that: The layered structural material in step 1 includes any one of iron-containing attapulgite and iron-based hydrotalcite, or a combination of the two.
3. The method for preparing the layered lattice iron bifunctional catalyst according to claim 1, characterized in that: The mass ratio of the layered structure material to deionized water is 1:1000 to 1:
100.
4. The method for preparing the layered lattice iron bifunctional catalyst according to claim 1, characterized in that: The mass of the layered structure material in step 1 is 1 to 25000 g.
5. The method for preparing the layered lattice iron bifunctional catalyst according to claim 1, characterized in that: The parameters of the nucleation reactor in step 1 are set as follows: stator and rotor slit width 0.05-0.5 mm, rotation speed 100-3000 rpm.
6. The method for preparing the layered lattice iron bifunctional catalyst according to claim 1, characterized in that: In step 2, the high temperature calcination temperature is 150-700° C., the insulation time is 1-5 hours, and the heating rate is 4-10° C. / min.
7. A layered lattice iron bifunctional catalyst, characterized in that The catalyst is prepared by the method for preparing the layered lattice iron bifunctional catalyst according to any one of claims 1 to 6.
8. The layered lattice iron bifunctional catalyst according to claim 7, characterized in that The layered lattice iron bifunctional catalyst has a Zeta potential of -32.26 to 45.16 mV and a specific surface area of 63.97 to 146.98 m 2 / g, and the pore size is 13.34~26.89nm.
9. The layered lattice iron bifunctional catalyst according to claim 7, characterized in that The molar ratio of divalent iron to trivalent iron in the layered lattice iron bifunctional catalyst is 0.54-1.
94.
10. Use of the layered lattice iron bifunctional catalyst according to any one of claims 7 to 9 in degrading and removing organic pollutants.
11. Use of the layered lattice iron bifunctional catalyst according to claim 10 in degrading and removing organic pollutants, characterized in that: The method for degrading and removing organic pollutants comprises the following steps: Step S1: Selecting organic pollutants, and adjusting the concentration and pH of the pollutant solution; Step S2: adjusting the temperature of the reaction system; Step S3: Add the layered lattice iron bifunctional catalyst into the pollutant solution, perform the first oscillation, and then add H2O2 to perform the second oscillation to make it react completely, thereby achieving the removal of organic pollutants.
12. Use of the layered lattice iron bifunctional catalyst according to claim 11 in degrading and removing organic pollutants, characterized in that: In step S1, the organic pollutant is a mixture of any one or more of methylene blue, methyl orange, Congo red, rhodamine B, tetracycline hydrochloride, doxycycline hydrochloride, ciprofloxacin, phenol, bisphenol A or 2,4-dichlorophenol; the concentration of the pollutant solution is adjusted to 10 to 30,000 mg / L, the volume is 0.05 to 2 L, and the pH of the pollutant solution is 2 to 14.
13. Use of the layered lattice iron bifunctional catalyst according to claim 12 in degrading and removing organic pollutants, characterized in that: The pH of the pollutant solution was adjusted using 1 M sulfuric acid or sodium hydroxide.
14. Use of the layered lattice iron bifunctional catalyst according to claim 11 in degrading and removing organic pollutants, characterized in that: In step S2, the temperature of the reaction system is 20-80°C.
15. Use of the layered lattice iron bifunctional catalyst according to claim 11 in degrading and removing organic pollutants, characterized in that: In step S3, the first oscillation time is 0 to 120 min; the purity of H2O2 is 10 wt.% to 30 wt.%, the mass fraction ratio of H2O2 to layered lattice iron bifunctional catalyst is 1:100 to 1:10; and the second oscillation time is 0 to 120 min.
16. Use of the layered lattice iron bifunctional catalyst according to claim 11 in degrading and removing organic pollutants, characterized in that: The method for degrading and removing organic pollutants also includes recovering the layered lattice iron bifunctional catalyst, specifically by filtering the layered lattice iron bifunctional catalyst mixed solution after the reaction through a 0.22 μm filter membrane, washing the residual organic matter on the surface with deionized water, and drying at 60° C. for 6 hours under vacuum conditions.
Citation Information
Patent Citations
Crystal face selective growth boehmite and preparation method thereof
CN111924865A
Cuy / MMgOx interfacial catalyst for selective alkyne hydrogenation and its preparation method
US20220234036A1
Cited By
Layered lattice iron bifunctional catalyst, preparation method therefor, and use thereof
WO2026137671A1